2014
DOI: 10.1016/j.simyco.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Pestalotiopsis revisited

Abstract: Species of Pestalotiopsis occur commonly as plant pathogens, and represent a fungal group known to produce a wide range of chemically novel, diverse metabolites. In the present study, we investigated 91 Pestalotiopsis isolates from the CBS-KNAW Fungal Biodiversity Centre (CBS) culture collection. The phylogeny of the Amphisphaeriaceae was constructed based on analysis of 28S nrRNA gene (LSU) sequence data, and taxonomic changes are proposed to reflect more natural groupings. We combined morphological and DNA d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
421
1
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 403 publications
(447 citation statements)
references
References 66 publications
(128 reference statements)
15
421
1
10
Order By: Relevance
“…In the review of the genus Pestalotiopsis, Maharachchikumbura et al (2014) made a phylogenetic reconstruction of the Amphisphaeriaceae based on analysis of LSU of the rRNA sequence data. Furthermore, two novel genera were segregated from Pestalotiopsis, namely Neopestalotiopsis and Pseudopestalotiopsis based on combined morphological and DNA data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the review of the genus Pestalotiopsis, Maharachchikumbura et al (2014) made a phylogenetic reconstruction of the Amphisphaeriaceae based on analysis of LSU of the rRNA sequence data. Furthermore, two novel genera were segregated from Pestalotiopsis, namely Neopestalotiopsis and Pseudopestalotiopsis based on combined morphological and DNA data.…”
Section: Discussionmentioning
confidence: 99%
“…Maharachchikumbura et al (2011) suggested that Pestalotiopsis should be adopted instead of Pestalosphaeria because it is an older and more common name. The genus Neopestalotiopsis was introduced by Maharachchikumbura et al (2014) as sexual morph not observed. The new species presently described is referred to as Neopestalotiopsis pernambucana and it is the first species of the genus encountered with the sexual morph.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…et al 2014Maharachchikumbura et al (2014 introduced this genus to accommodate several Pestalotiopsis species which did not cluster in Pestalotiopsis sensu stricto. This placement was confirmed by Wijayawardene et al (2016).…”
Section: Catenulomyces Egidi and De Hoogmentioning
confidence: 99%
“…The microscopic characters were studied using a polarizing optical microscope (Olympus BX-51 P) coupled with charge-coupled device camera and measurements carried out using image J software. At least 30 observations were made per structure [7,8]. The potential solvent extract was separated on silica plates using thin-layer chromatography using solvent hexane:methanol (70:30).…”
Section: Introductionmentioning
confidence: 99%